PENGARUH KEBIASAAN BERMAIN GAME ON LINE TERHADAP KREATIVITAS BELAJAR KELAS VIII SMP MUHAMMADIYAH 1 PONTIANAK - Anisa, Nyaik; Asrosi, Asrosi; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:The development of the technology increase and makes poeople using technology almost in every aspect. With this development, itâ€™s can be easier people for doing activities. Includes game, through playing games, the children may learn from games that they have used. Even, their creativities increase with those game and can using the game well. The main aim of this research for getting some information and description clearly about the effects of playing games on line for students class 8th in SMP Muhammadiyah 1 Pontianak. Population in this research is 89 students class 8th in SMP Muhammadiyah 1 Pontianak. This research using quantitative approach. This technique using analysis percentage form and product correlation and coefficient determination. Based on this research, the result is: (1) the habit of the students which playing games online class 8th in SMP Muhammadiyah 1 Pontianak is â€œenoughâ€ (2) the creativities of the students class 8th in SMP Muhammadiyah 1 Pontianak is â€œenoughâ€ (3) there are some effect between the habit playing games on line and the creativities of the students class 8th in SMP Muhammadiyah 1 Pontianak. Â Keywords: On Line Game, Studying Creativity